Supported Lipid Bilayers and the Study of Two-Dimensional Binding Kinetics - Dam, Tommy; Chouliara, Manto; Junghans, Victoria; Jönsson, Peter (Frontiers in Molecular Biosciences, 2022)
Binding between protein molecules on contacting cells is essential in initiating and regulating several key biological processes. In contrast to interactions between molecules in solution, these events are restricted to the two-dimensional (2D) plane of the meeting cell surfaces. However, converting between the more commonly available binding kinetics measured in solution and the so-called 2D binding kinetics has proven a complicated task since for the latter several factors other than the protein-protein interaction per se have an impact. A few important examples of these are: protein density, membrane fluctuations, force on the bond and the use of auxiliary binding molecules. The development of model membranes, and in particular supported lipid bilayers (SLBs), has made it possible to simplify the studied contact to analyze these effects and to measure 2D binding kinetics of individual protein-protein interactions. We will in this review give an overview of, and discuss, how different SLB systems have been used for this and compare different methods to measure binding kinetics in cell-SLB contacts. Typically, the SLB is functionalized with fluorescently labelled ligands whose interaction with the corresponding receptor on a binding cell can be detected. This interaction can either be studied (i) by an accumulation of ligands in the cell-SLB contact, whose magnitude depends on the density of the proteins and binding affinity of the interaction, or (ii) by tracking single ligands in the SLB, which upon interaction with a receptor result in a change of motion of the diffusing ligand. The advantages and disadvantages of other methods measuring 2D binding kinetics will also be discussed and compared to the fluorescence-based methods. Although binding kinetic measurements in cell-SLB contacts have provided novel information on how ligands interact with receptors in vivo the number of these measurements is still limited. This is influenced by the complexity of the system as well as the required experimental time. Moreover, the outcome can vary significantly between studies, highlighting the necessity for continued development of methods to study 2D binding kinetics with higher precision and ease.